O discurso erótico: a construção social do erotismo e sua influência na sexualidade - Marino, Sueli (2013)
This study aims to comprehend the changes on the discourses and practices of sexuality considering the transformations that occurred in the last decades. Under the principles of the Systemic thinking and Social Construccionism, we seek to understand how the discourse and discursive practices about eroticism and sexuality are presented comparatively in two distinct historical moments in the two versions of the film Lolita, in 1962 and 1997, and that refer to the manifestations of desire and pursuit of pleasure. A qualitative analyzes was done with emphasis on the social poetics highlighting the defining moments of each segmentation of the movie that were then forwarded to units of meaning. We emphasize throughout this process that the definition of eroticism cannot be considered isolated from the contexts and the linguistic communities that establish the meaning of this dialogue and how the social constructions are inserted in a particular time and culture that also change over time